SUNGAI DALAM PEMAKNAAN MASYARAKAT PEDESAAN STUDI ETNOEKOLOGI KOMUNIKASI PADA MASYARAKAT DESA KARANG ANYAR, BANYUASIN, SUMATERA SELATAN - Yenrizal Yenrizal (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
Karang Anyar village communities are communities living on the side of Telang River, Banyuasin, South Sumatra. Despite already spread to the middle of the land, but the original settlement remain in the river. Since ancient times this settlement remains intact, never affected, especially the threat of flooding. This fact is interesting because it gives a complete picture that was in the river does not cause problems, although the river was often overflowing. This research was conducted using ethnoecology approach to communication, which is intended to capture the meaning of community viewpoints on the local environment. These results indicate that there is a process of meaning that are symbolic of the community on the local environment which is marked with the meaning of the river, borders, settlements, and plants growing around it. These meanings inherent in all activities of the community in Karang Anyar.